2009
DOI: 10.1186/1471-2407-9-438
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor coregulator SNP discovery and impact on breast cancer risk

Abstract: BackgroundCoregulator proteins are "master regulators", directing transcriptional and posttranscriptional regulation of many target genes, and are critical in many normal physiological processes, but also in hormone driven diseases, such as breast cancer. Little is known on how genetic changes in these genes impact disease development and progression. Thus, we set out to identify novel single nucleotide polymorphisms (SNPs) within SRC-1 (NCoA1), SRC-3 (NCoA3, AIB1), NCoR (NCoR1), and SMRT (NCoR2), and test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Current studies have shown that the breast cancer risks are associated with commonly occurring single nucleotide polymorphisms (SNPs) [2832]. The table SNP (131) (dbSNP build 131) in UCSC (http://genome.ucsc.edu/) was used to identify SNPs near the ER binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies have shown that the breast cancer risks are associated with commonly occurring single nucleotide polymorphisms (SNPs) [2832]. The table SNP (131) (dbSNP build 131) in UCSC (http://genome.ucsc.edu/) was used to identify SNPs near the ER binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…82 A SRC-3 SNP has been identified that predicts response to chemotherapy for lymphoblastic lymphomas and another SRC-3 SNP has been linked to breast cancer risk. 83,84 Our speculation is that coregulator dysfunction will not be restricted solely to rare genetic conditions such as highly penetrant monogenic genetic diseases. By contrast, many coregulators, including all three SRC coregulators, are not essential for viability and even their complete knockout is not lethal.…”
Section: Coregulator ‘Omics’mentioning
confidence: 99%
“…Under both physiological and pathological conditions, SRC-1 was shown to play an important role in the maintenance of bone mineral density by sex hormones and is necessary for protection against osteopenia and osteoporosis 66 . Interestingly, a genetic polymorphic variant of the SRC-1 protein (SNP-1272S) was found to be associated with a decrease in bone mineral density 52 , 67 .…”
Section: Biological Functions Of Src-1mentioning
confidence: 99%